Pengaruh Perbandingan Komposisi Antara Limbah Baglog dengan Kotoran Sapi Menggunakan EM-4 - Paramita Dwi Sukmawati; Angge Dhevi Warisaura (Fakultas Teknik, 2022)
UKM Jamur Raya is one of the industries that produce oyster mushrooms and is located in the village of Gesikan, Subdistrict of Gantiwarno, Regency of Klaten. The production carried out by UKM Jamur Raya is the manufacture of mushroom seeds until the planting of mushroom seeds in baglog. During the planting process, it will produce waste as a leftover baglog. Baglog waste, if only disposed of, will cause environmental problems and problems for mushroom cultivation. For this reason, it is necessary to treat baglog waste, and when viewed from the content of baglog waste, one thing that can be done is to process baglog waste into compost. The composting method used in this research is vermicomposting, which is making compost by adding worms. There are several factors in composting, one of which is the ratio of C/N values. If the organic matter is still not appropriately decomposed, then the C/N value is large and vice versa. Nitrogen content in baglog waste is very small at 0.6%, so additional materials are needed that can be used as a nitrogen source, one of which is cow dung. The most optimal vermicomposting results are found in the comparison of the composition between baglog waste and cow dung of 5 kg of baglog waste : 2.5 kg of cow dung with a C content value of 0.522%, a N content value of 20.18%, and a C/N ratio value of 20.18%.